2012
DOI: 10.1021/la301232r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Doping on Hydrogen Storage Capacity of Palladium Decorated Graphene

Abstract: A high hydrogen storage capacity for palladium decorated nitrogen-doped hydrogen exfoliated graphene nanocomposite is demonstrated under moderate temperature and pressure conditions. The nitrogen doping of hydrogen exfoliated graphene is done by nitrogen plasma treatment, and palladium nanoparticles are decorated over nitrogen-doped graphene by a modified polyol reduction technique. An increase of 66% is achieved by nitrogen doping in the hydrogen uptake capacity of hydrogen exfoliated graphene at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
135
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(139 citation statements)
references
References 62 publications
2
135
0
2
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26] The metals mostly used in those investigations are alkali metals 18,19 and some transition metals like vanadium, palladium, and platinum. [22][23][24][25][26][27] To explain the observed enhancement of the hydrogen adsorption, a mechanism of spillover 28,29 has generally been assumed. [22][23][24][25][26][27]30,31 In that mechanism, the hydrogen molecules are first adsorbed and dissociated on the surface of the metallic nanoparticles, and are next transported onto the surface of the substrate carbon material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26] The metals mostly used in those investigations are alkali metals 18,19 and some transition metals like vanadium, palladium, and platinum. [22][23][24][25][26][27] To explain the observed enhancement of the hydrogen adsorption, a mechanism of spillover 28,29 has generally been assumed. [22][23][24][25][26][27]30,31 In that mechanism, the hydrogen molecules are first adsorbed and dissociated on the surface of the metallic nanoparticles, and are next transported onto the surface of the substrate carbon material.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] To explain the observed enhancement of the hydrogen adsorption, a mechanism of spillover 28,29 has generally been assumed. [22][23][24][25][26][27]30,31 In that mechanism, the hydrogen molecules are first adsorbed and dissociated on the surface of the metallic nanoparticles, and are next transported onto the surface of the substrate carbon material. However, in our opinion, the validity of that spillover idea has not been scrutinized critically.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31] In many of these studies H 2 sorption was reported for single sample and using only one sorption isotherm, without analysis of reproducibility of sorption in several cycles. Theoretical studies do not predict exceptional H 2 sorption for graphene by physisorption relative to other carbon materials with comparable SSA.…”
Section: Introductionmentioning
confidence: 99%
“…Pt, Pd, TiO 2 ) provides increase of hydrogen sorption by 10-500%. [28,31,37] In some studies the hydrogen storage values which satisfy and even exceed DOE targets have been reported for temperatures near ambient and assigned to "spillover" mechanism. For example, Parambhath et al reported uptake of ~3wt% for Pd decorated material with SSA of ~470 m 2 /g already at 40bar H 2 pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In physical storage routes, hydrogen compressed under high pressure or stored in a liquid state can achieve attractive volumetric density, but these technologies suffer from extremely harsh processing conditions at a very high cost with severe safety concerns. On the other hand, although hydrogen can be stored in porous materials via adsorption under mild conditions [5][6][7][8][9], the relatively low hydrogen storage capacity of various sorbents seems to be an insurmountable obstacle for practical applications. A great deal of attention has been paid to the chemical storage of hydrogen, and various types of hydrogen storage systems have been intensively studied based on different hydrogen carriers such as metal and organic hydrides [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%